HIGH MANTLE TEMPERATURE DURING CRETACEOUS AVALANCHE - Machetel P.; Humler E. (My University, 2003)
A new sequence of axisymmetrical spherical mantle convection simulations has been computed to monitor the influence of mantle avalanches on the mantle thermal state. During an avalanche that is characterized by a high rate of mixing between upper mantle and lower mantle, a complex perturbation of the thermal field occurs due to the advection of cold upper mantle into the lower mantle, and the hot return flows from the lower mantle. The computation shows that the avalanches trigger global upper mantle warming of several tens of degrees and make it possible to explain both core-mantle boundary and transition zone origins for mantle plumes. Recently, the chemical compositions of DSDP/ODP drill holes on crust older than 80 Myr have been interpreted to reflect a higher mean mantle temperature during the Mesozoic [Humler et al., Earth Planet. Sci. Lett. 173 (1999) 7-23]. Here, we have used and extended the data set for oceanic crust younger than 80 Myr. Combining the mean chemistry for old oceanic crust and the mean depth of the ocean basin versus the square root of age, we propose a continuous curve for the temperature evolution of the upper mantle for the last 130 Myr. It shows a mantle thermal high around 125 Ma with amplitude (50 K) and duration (30 Myr) comparable with those obtained from theoretical convection models. It is proposed that such a high mantle temperature may be due to the thermal effects of an avalanche which may have started 180 Myr ago.
Keywords: MANTLE CONVECTION; AVALANCHE; TEMPERATURE; ISOSTASY; GEOCHEMISTRY; Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая